Bioaerosol release from composting facilities - Mohamed Taha, M. P. B (Cranfield University, 2005)
The use of composting is expected to increase dramatically due to its economic and environmental benefits. For public health protection, regulators and licensing authorities are requesting risk assessments to be conducted prior to the development and operation of composting. Significant amounts of microrganisms can be aerosolised and transported by winds to points of exposure. However, the source term factors that influence their release and their dispersal are not fully understood. In this thesis a method to measure viable bioaerosols emission rates from static compost pile surfaces and during the agitation of compost was developed. The factors that influence the emission of bioaerosols from compost piles of different ages and during different agitation activities were evaluated. A wind tunnel analysis was successfully used to measure the surface flux bioaerosols emission rate. Newly estimated emission rates from various source terms were then modelled to produce source depletion curves. The surface emission flux of a static pile was estimated to be 102 to 104cfu/m2/s for both A. fumigatus and actinomycetes. The turning of compost releases the highest bioaerosols concentration range from 104 to 108cfu/s compared with the shredding and screening. The turning of an early stage compost windrow emitted the highest amount of bioaerosols. This study introduces a new method for quantifying bioaerosols dispersal, thus improving the risk assessments required for environmental permitting.